A study on the use of visual aids in teaching English vocabulary for 3rd grade schoolers = Nghiên cứu về việc sử dụng giáo cụ trực quan trong việc dạy từ vựng tiếng Anh cho học sinh lớp 3. M.A Thesis Linguistics: 60 14 10 - Tran, Thi Nhung (2019)
This study was implemented to find the impacts of using visual aids in teaching English Vocabulary for the third grade students. The method the researcher used to study is Action Research (AR). Firstly, the result of the study proved that using visual aids in teaching improved third grade students‟ vocabulary mastery in listening, understanding, speaking and writing. However, it was found that in the second intervention the students‟ improvement was often in Part 1 of the test – Listening and number/choose.